2020
DOI: 10.3389/fonc.2020.01151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiomics-Based Machine-Learning Classifiers in Diagnosis of Glioblastoma From Primary Central Nervous System Lymphoma

Abstract: The purpose of the current study was to evaluate the ability of magnetic resonance (MR) radiomics-based machine-learning algorithms in differentiating glioblastoma (GBM) from primary central nervous system lymphoma (PCNSL). Method: One-hundred and thirty-eight patients were enrolled in this study. Radiomics features were extracted from contrast-enhanced MR images, and the machine-learning models were established using five selection methods (distance correlation, random forest, least absolute shrinkage and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Increasingly data is evolving showing that ML-based imaging analysis is vulnerable to feature selection [ 61 , 63 ]. In a recent study where radiomics-based ML algorithms in Differentiating Glioblastoma (GBM) from primary central nervous system lymphoma (PCNSL) were evaluated, 5 selection methods (distance correlation, random forest, Least Absolute Shrinkage and Selection Operator (LASSO), eXtreme gradient boosting (Xgboost), and Gradient Boosting Decision Tree) and 3 radiomics-based ML classifiers Linear Discriminant Analysis (LDA), Support Vector Machine (SVM), and Logistic Regression (LR)) were compared [ 63 ]. The authors noted that the most optimal discriminative performance was observed among all classifiers when combined with the suitable selection method.…”
Section: Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly data is evolving showing that ML-based imaging analysis is vulnerable to feature selection [ 61 , 63 ]. In a recent study where radiomics-based ML algorithms in Differentiating Glioblastoma (GBM) from primary central nervous system lymphoma (PCNSL) were evaluated, 5 selection methods (distance correlation, random forest, Least Absolute Shrinkage and Selection Operator (LASSO), eXtreme gradient boosting (Xgboost), and Gradient Boosting Decision Tree) and 3 radiomics-based ML classifiers Linear Discriminant Analysis (LDA), Support Vector Machine (SVM), and Logistic Regression (LR)) were compared [ 63 ]. The authors noted that the most optimal discriminative performance was observed among all classifiers when combined with the suitable selection method.…”
Section: Segmentationmentioning
confidence: 99%
“…For LDA-based models, the optimal one was Distance Correlation + LDA with AUC of 0.978. For SVM-based models, Distance Correlation + SVM was the one with highest AUC of 0.959, while for LR-based models, the highest AUC was 0.966 established with LASSO + LR [ 63 ]. In a literature review spanning 2013 to 2018, LR and LASSO were the two most used techniques for feature selection [ 64 ].…”
Section: Segmentationmentioning
confidence: 99%
“…The feature selection and model-building methods vary significantly among studies (see Table S1), and in some cases, the models include clinical or semantic variables. MRI sequences used for tumor differentiation vary as well and have, for example, CE T1 sequences only [46,52,54] as well as combinations of ADC and T1CE [55]; ADC, FLAIR, and CE T1 [47]; DWI, CE T1, and FLAIR [48]; CE T1, T2 and DWI [50]; T1, T2, and FLAIR [51,56]; or ADC and gradientecho [15]. A study involving 141 patients reported over 90% accuracy in differentiation between various tumor entities, including GBM, lymphoma, BM, and meningioma, using five MRI sequences in total [15].…”
Section: Primary Cns Lymphomamentioning
confidence: 99%
“…A recent meta-analysis assessing the utility of ML models for PCNSL diagnosis reports 0.878 as the lowest AUC across eight studies [61]. Another prospectively validated model reported an AUC of 0.978 using only T1 weighted images [62]. ML-based algorithms have advantages of being open access, easily accessible, and minimal reliance on novel machines or software.…”
Section: Machine Learning: Better Analysis Of Conventional Mri Meta-datamentioning
confidence: 99%